Peningkatan Motivasi dan Kiat Belajar Inflasi Melalui Proses Belajar di Madrasah Aliyah Babussalam Alahan Kae Ulu Pungkut - Ahmad Fadlan (Cattleya Darmaya Fortuna, 2020)
The formulation of the problem in this study is Is There an Effort to Increase Motivation and Tips for Learning Inflation Through the Learning Process in Madrasah Aliyah Babussalam Alahan Kae Ulu Pungkut? In general, the purpose of this study is to describe the Improvement of Motivation and Tips for Learning Inflation Through the Learning Process in the Madrasah Aliyah Babussalam Alahan Kae Ulu Pungkut. This type of research used by the author in this study is an associative method, because associative research is research that aims to determine the relationship between two or more variables, which are able to explain and look for an overview of the two variables, and see the effect of them. The method used is the method of literature and field studies. The hypothesis testing technique used in this study is to use the moment product correlation formula. Obtained rxy1 count = 0.672 and rxy2 count = 0.645. It can be seen that r count is greater than the value of r table with an error rate of 5%, namely 0.672> 0.349 for rxy1 and 0.645> 0.349 for rxy2. Thus it can be concluded that, There is an Effort to Improve Motivation and Tips for Learning in Schools Through the Teaching Process in the Field of Economics Economics Subject Material Price and Inflation, Demand and Supply of Student Money in Class XI Madrasah Aliyah Babussalam Alahan Kae Ulu Pungkut